FOCUS: the development of a community of academic leaders - Lina Prada Angarita; Nayibe Rosado Mendinueta; Katina katinac@uninorte.edu.co (Academic Chairpersons Conference Proceedings, 2023)
This presentation reports the development of a community of practice for academic leaders in Colombia, South America. Document analysis from 2016 to 2020 helped to characterize the nature of the activities, the purposes, the products and gains. There is evidence of a change of purpose, agency and awareness.
Keywords: Professional Development; community of practice; leadership; higher education; university based-development.